2012
DOI: 10.5897/ijps11.414
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different ratios of auxin and cytokinin for the in vitro propagation of Streptocarpus rexii Lindl.

Abstract: A successful means of in vitro propagation of Streptocarpus rexii Lindl. using leaf tissue as the explants is described. Secondary explants were placed on several regeneration media supplemented with various concentrations of indole-acetic acid (IAA) and benzyladenine (BA). Optimal shoot proliferation was obtained on Murashige and Skoog basal media containing 0.1 mg/L IAA in combination with 0.5 mg/L BA. The growth of explants, as quantified by their fresh and dry weights, was significantly higher in the 1 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…A shoot height at a statistically high level was also obtained under the influence of red light (R-5.83), red with blue (RB-5.33), the addition of green (RBG-5.47) LED and under fluorescence (Fl-6.53). In the studies carried out to date on plant in vitro cultures of Streptocarpus by various authors, there have been no reported studies that have examined the effect of different quality of LED light on its developmental parameters [13,[35][36][37]. Moreover, as for the in- In the studies carried out to date on plant in vitro cultures of Streptocarpus by various authors, there have been no reported studies that have examined the effect of different quality of LED light on its developmental parameters [13,[35][36][37].…”
Section: Biometrical Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A shoot height at a statistically high level was also obtained under the influence of red light (R-5.83), red with blue (RB-5.33), the addition of green (RBG-5.47) LED and under fluorescence (Fl-6.53). In the studies carried out to date on plant in vitro cultures of Streptocarpus by various authors, there have been no reported studies that have examined the effect of different quality of LED light on its developmental parameters [13,[35][36][37]. Moreover, as for the in- In the studies carried out to date on plant in vitro cultures of Streptocarpus by various authors, there have been no reported studies that have examined the effect of different quality of LED light on its developmental parameters [13,[35][36][37].…”
Section: Biometrical Observationsmentioning
confidence: 99%
“…In the studies carried out to date on plant in vitro cultures of Streptocarpus by various authors, there have been no reported studies that have examined the effect of different quality of LED light on its developmental parameters [13,[35][36][37]. Moreover, as for the in- In the studies carried out to date on plant in vitro cultures of Streptocarpus by various authors, there have been no reported studies that have examined the effect of different quality of LED light on its developmental parameters [13,[35][36][37]. Moreover, as for the influence of light alone on the biometrics of proliferated plants of different species, the majority of analyses carried out by various authors concern the effect of red and blue LED light and their combinations in various proportions ( [21,[38][39][40][41][42] and many others).…”
Section: Biometrical Observationsmentioning
confidence: 99%